y = a + b / x where a , b are real numbers, if y = 1 when x = -1 and y = 5 when x = -5, then a +b equals

a. -1 b. 0 c. 11 d . 10

Subtracting (1) from (2) we get

putting the value of a in (1) we get

*b* = 5

∴ *a* + *b* = 6 + 5 = 11

**
**

y = a + b / x where a , b are real numbers, if y = 1 when x = -1 and y = 5 when x = -5, then a +b equals

a. -1 b. 0 c. 11 d . 10

Subtracting (1) from (2) we get

putting the value of a in (1) we get

*b* = 5

∴ *a* + *b* = 6 + 5 = 11

**
**

What are you looking for?